E-115 Intracranial salvage techniques in refractory thrombectomy: who, when and how?. (22nd July 2019) - Abdalla, R; Darwish, M; Shokuhfar, T; Azmi, S; Cantrell, D; Hurley, M; Potts, M; Jahromi, B; Shaibani, A; Ansari, S
Abstract : Purpose: Emergent large vessel occlusion due to underlying vessel wall pathology may be refractory to the endovascular stroke thrombectomy requiring further intracranial interventions to achieve successful recanalization. The aim of our study was to determine the prevalence of refractory thrombectomy requiring further intervention, compare their baseline characteristics, adjunctive intracranial interventions, and outcomes. Methods: We retrospectively reviewed 253 patients treated with mechanical thrombectomy for ELVO from Jan 2015 to December 20198. Refractory thrombectomy was defined as patients requiring emergent intracranial angioplasty/stenting, intraprocedural antiplatelet therapy, or patients suffering reocclusion in the same artery within one day of the procedure. Baseline characteristics and outcomes were compared between the refractory and the standard treatment groups using Mann-Whitney and Fisher Exact and Chi square tests. Outcomes were also compared within the refractory group undergoing different treatment modalities. Favorable outcome was defined as mRS ≤ 2 after 3 months. Results: Refractory thrombectomy was identified in 22 cases (8.7%) with no statistically significant differences in baseline characteristics, median NIHSS score (15 vs. 17, P=0.14), and percentage of favorable outcomes (42.1% vs 51.9%, P=0.48) versus the standard thrombectomy group, respectively. Patients in the refractory cohort had a significantly higher prevalence of diabetes (45.5% vs. 19.9%, P=0.013), while the standard group patients presented with significantly higher rates of atrial fibrillation (47.8% vs. 18.2%, P=0.007). Diabetes was the sole independent predictor of refractory thrombectomy with OR 3.436 (95% CI: 1.190–9.524, p=0.017). Within the refractory group, 9 patients were treated with intracranial stenting (40.9%), 7 received intra-arterial/intravenous eptifibatide infusion (31.8%), 2 patients were treated by angioplasty (9%), and 4 developed silent re-occlusions (18%). There were no significant differences in favorable outcomes between the standard versus refractory thrombectomy groups, whether treated with intracranial stenting or eptifibatide antiplatelet therapy (51.9% Vs. 62.5% Vs. 14.3%, P=0.12). Conclusion: Refractory thrombectomy is more common in diabetics. Emergent intracranial stenting and eptifibatide antiplatelet are equally safe and effective adjuvant treatments after stroke thrombectomy in the setting of underlying vessel wall pathology. Disclosures: R. Abdalla: None. M. Darwish: None. T. Shokuhfar: None. S. Azmi: None. D. Cantrell: None. M. Hurley: None. M. Potts: None. B. Jahromi: None. A. Shaibani: None. S. Ansari: None.